Development of In-Vitro cell based assay for the determination of biological activity of FSH using a CHO based recombinant cell line - Patel, Ravish; Mody, Rustom (Research in Biotechnology, 2013)
The In-Vitro bioassay was developed for the determination of biological activity of Follicle Stimulating Hormone (FSH) using recombinant Chinese hamster ovary (CHO) based cell line that expresses the human FSH receptor (CHOSI FSHR CRELuc B-5) as well as luciferase reporter construct. The signal measured here comes from the luciferase activity that is dependent on the FSH stimulation. The present work focuses on an In-Vitro receptor-binding assay in which binding of FSH to its receptors (expressed on CHO cells) gives a dose and/or activity-dependent production of cAMP quantified by luciferase assay system. This kind of In-Vitro bioassay is used to determine the biological potency of FSH molecule. The assay is simple, has high throughput (performed in 96 half well area plates), and shows reproducible dose-response curves in the concentration range of 10.5-0.02 mIU/mL. With overall repeatability 6.5% and spike recovery of 100.7% and the assay has high precision and accuracy. Specificity was demonstrated by the lake of activity of assaying a variety of proteins manufactured by Intas. The In-Vitro cell based reporter gene assay has the preferred characteristics which makes it suitable to determine the biological activity of Recombinant Human Follicle Stimulating Hormone rHuFSH.